INJURIES IN RAILWAY TRANSPORT AND WAYS OF REDUCING THE INDUSTRIAL DANGERS IMPACT - Moroz, М.; Mykhailova, Е.; Rohozin, А.; Skrypnyk, О. (Municipal economy of cities. Series: «Economy science», 2023)
The article deals with the problem of the labour protection state in railway transport. The transport sector, in particular the railway, is one of the main country's activity spheres, which significantly affects the level of its social and economic development. The analysis of statistical data shows that the transport industry is one of the leaders in the most trauma-hazardous human activity spheres. Thus, the analysis of injury rates and factors determining the professional reliability of locomotive crews, and the scientific substantiation of measures set aimed at preserving the health of railway transport workers and ensuring the safety of railway transport, are urgent and essential tasks. The article's purpose is a comprehensive analysis of the injury's actual state in railway transport. In the work, it is established that during the performance of their duties, railway transport employees are affected by physical, chemical and biological harmful production factors. The work is carried out under the influence of psychophysiological factors caused by the severity and intensity of the labour process in conditions of hydrodynamic and fixed working posture. It was determined that the influence of adverse factors complex leads to disruption of the cardiovascular, central nervous and endocrine systems activity. The authors assessed the actual state of industrial and non-industrial injuries in railway transport. It has been established that the number of industrial accident victims has been gradually increasing in recent years. This indicates the need to develop and implement in practice a set of measures to improve the working conditions of mainline locomotive crews. It is noted that the key areas of measures to preserve the health and professional capacity of railway transport workers are the improvement of regulatory and legal support, socio-economic motivation of workers, and organizational-technological and sanitary-medical measures.